Pengaruh Intervensi Konseling Feeding Rules dan Massage Eating Difficulties dalam Mengatasi Kesulitan Makan Balita di Kelurahan Cangkiran Mijen Semarang: The Effect of Feeding Rules Counselling and Eating Difficulty Massage to Overcome Eating Problems in Toddlers in Cangkiran Mijen, Semarang - Putri Deyya, Tiaradita; Qomariyah; Maya Cobalt Angio (Universitas Ngudi waluyo, 2024)
Toddlers aged 1-5 years are a group that is vulnerable to nutritional problems. During this period, they experience very rapid growth and development. Toddlers usually have difficulty eating because of the increasing activities such as playing and running. While in toddlers, there is a process of growth and development that requires adequate nutrition. Efforts to overcome eating difficulties can be done with basic rules for feeding with Feeding Rules and pharmacological efforts with Massage Eating Difficulties. The purpose of the study was to determine the effect of counseling on feeding rules and massage eating difficulties on overcoming eating difficulties in toddlers. The research design used Experimental research with a One group Pre-Test and Post-test design approach model. The population of this study were toddlers aged 1-5 years who experienced weight gain in Cangkiran Mijen Village, Semarang. The sampling technique used Purposive Sampling and the number of samples obtained was 45 toddlers. The statistical test used was Mc Nemar from the results obtained p value = <0.001, then Ha was accepted, meaning that there was an Effect of Counseling on Feeding Rules and Massage Eating Difficulties on eating difficulties in toddlers in Cangkiran Mijen Village, Semarang. It is hoped that this research can be applied by health services including midwives as one of the complementary actions or interventions that can be carried out in providing midwifery care to toddlers in overcoming eating difficulties in toddlers. Abstrak Anak balita yang berusia 1-5 tahun merupakan kelompok yang rawan terhadap masalah gizi, Pada masa ini mengalami pertumbuhan dan perkembangan yang sangat pesat. Balita biasanya menjadi sulit makan karena semakin bertambahnya aktivitas seperti bermain dan berlari. Sedangkan pada balita terjadi proses pertumbuhan dan perkembangan yang membutuhkan kecukupan nutrisi. Upaya untuk mengatasi kesulitan makan dapat dilakukan dengan aturan dasar pemberian makan dengan Feeding Rules dan upaya farmakologi dengan Massage Eating Difficulties. Tujuan penelitian ntuk mengetahui Pengaruh konseling feeding rules dan massage eating difficulties terhadap mengatasi kesulitan makan pada balita. Rancangan penelitian menggunakan penelitian Experimental dengan model pendekatan One group Pre-Test and Post-test design. Populasi dari penelitian ini adalah balita berusia 1-5 tahun yang mengalami berat badan tidak naik di Kelurahan Cangkiran Mijen Semarang. Teknik pengambilan sample dengan Purposive Sampling dan didapatkan jumlah sampel sebesar 45 balita. Uji statistic yang digunakan adalah Mc Nemar dari hasil didapatkan nilai p value = <0,001, maka Ha diterima, artinya ada Pengaruh Konseling Feeding Rules dan Massage Eating Difficulties terhadap kesulitan makan pada balita di Kelurahan Cangkiran Mijen Semarang. Diharapkan penelitian ini dapat diaplikasikan oleh pelayanan Kesehatan termasuk Bidan sebagai salah satu Tindakan atau intervensi komplementer yang dapat dilakukan dalam memberikan asuhan kebidanan pada anak balita dalam mengatasi kesulitan makan pada anak balita.